Evaluation of bio-refinery alternatives to produce sustainable aviation fuels in a sugarcane mill. (1st August 2022) - Tanzil, Abid H; Brandt, Kristin; Zhang, Xiao; Wolcott, Michael; Silva Lora, Electo Eduardo; Stockle, Claudio; Garcia-Perez, Manuel
Highlights: Twenty biorefinery concepts for the production of Sustainable Aviation Fuels (SAFs) in a 12, 444 MT sugarcane mill were studied. Five SAF technologies were analyzed. Fourteen out of fifteen scenarios resulted in capital reductions (5 to 86%). We identified MFSPs reductions between 8 and 53%. Twelve scenarios yielded GHG savings from 10 to 100%. Abstract: A large sugarcane mill with a processing capacity of 12, 444 metric ton sugarcane per day is used as a host plant for the evaluation of several bio-refinery concepts to produce sustainable aviation fuels (SAF). Five SAF technologies are studied: Virent's BioForming, alcohol to jet, direct sugar to hydrocarbon, fast pyrolysis-bio-oil hydrotreatment, and gasification & Fischer-Tropsch technologies. A standardized methodology is followed to evaluate twenty integrated scenarios to produce fuels using sugarcane mill facilities. In our analyses we assumed that the sugarcane mill operates 6 months but that the SAF unit operates twelve months (with switchgrass, molasses, and ethanol purchases). For each of the scenarios, the minimum fuel selling price (MFSP) and greenhouse gas emissions (GHG) within the integrated scenarios are estimated. Fourteen out of fifteen integrated scenarios resulted in reductions of capital (5 to 86 %) and operational costs (4 to 34 %) compared with the base case processes. These benefits are associated with a better use of sugarcane mill's infrastructure, co-products availability (molasses and ethanol) as well as waste stream feedstocks (surplus bagasse). It was possible to identify conditions reducing MFSPs between 8 and 53 % from corresponding base cases. Twelve scenarios yielded GHG savings from 10% to 97%.